Neurowaves : brain, time, and consciousness - Northoff, Georg (McGill-Queen's University Press, 2023)
"The connection of the brain to the mind remains one of the most persistent mysteries in philosophy and neuroscience. Georg Northoff proposes a new approach to the so-called mind-body problem, drawing on an insight from physics: time structures all objects and events in the world, and all objects and events are in dynamic relationship. This also shapes the brain as it is part of the dynamic of the world as whole. In Neurowaves Northoff posits that the entire world is structured by waves of time and argues that the passing of these waves through our brains--neurowaves--produces mental experience. The brain's neural waves transform into mental waves; time and its dynamics are shared by brain and mind as their common currency. Like in physics and biology that radically changes our view. Copernicus showed how the earth moves, and that its movements are just a tiny part of the universe's passage of time. Darwin showed that the human species is one among many species passing through evolution's timescales. Northoff calls for another Copernican revolution, replacing the mind-body problem with questions about the temporal-dynamic relationship between brain and world. Illustrated with vivid examples from different facets of the physical and biological world, Neurowaves provides captivating insights and an innovative, entertaining unravelling of the temporal connection of brain and mind."--